Sekolah Orang Tua Hebat sebagai Media Edukasi Pengasuhan Anak di Kelurahan Keputih Surabaya: Sebuah Praktik Pengabdian KKN Unitomo - Simanjuntak, Nensy Megawati; Lukmansyah, Ferdy; Vancelin, Nathania Mariany; Mustika Sari, Dessy Nur; Ramadhan Pi, Muhamad Taufik; Fiqri, ⁠Alvian Hikmal; Saputro, Bima Dwi; Maheswara, M Reno Adwitiya Putra (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2025)
Abstract: The Great Parents School Program is a community empowerment effort to improve family parenting capacity. This activity is implemented through the Unitomo Community Service Program (KKN) in Keputih Village, Surabaya, with the aim of educating parents about positive parenting patterns, effective communication within the family, and strengthening the role of parents as the first and primary educators of children. The implementation method uses a participatory approach through counseling, focus group discussions, and simulations of parenting practices relevant to community needs. Results indicate that participants gain a new understanding of adaptive parenting strategies, are able to reflect on their roles within the family, and have basic skills to implement healthier and more communicative parenting patterns. Furthermore, this activity strengthens collaborative relationships between universities and the community in creating resilient, community-based families. Thus, the Great Parents School can serve as a sustainable educational platform for the community, particularly in supporting optimal child growth and development. Keywords: Great Parents School, parenting, KKN, community empowerment, Keputih Surabaya